ANALYSIS OF THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE ON COMPANIES LISTED IN EXCHANGE INDONESIAN SECURITIES - Kaharudin Kaharudin; Maria Lusiana Yulianti; Andrew Shandy Utama (Jurnal Ekonomi, 2023)
This study aims to decide on the Impact Testing of Corporate Social Responsibility on the Execution of Monetary Organization Recorded in Exchange Effect Indonesia. Studies use quantitative spellbinding methodology, hoping to break the relationship between at least two factors. The number of residents in this study is organizations listed on the Indonesia Stock Exchange year 2018-22020, that is as much 30 organizations. For Example study, this is 30 organizations multiplied for 3 years with the aim of the sample in this study being 90 information. Procedure The investigation used is an examination of the recurrence of information boards. Reasonability test with use test t factual directed on a number of matter for test influence Among Variable Dependent and dependent variable with the assumption that different factors are seen as fixed. Judging from the consequences of the t-test presented in table 4.9 above, Corporate Social Responsibility (X) has a t count of 2.566144 with an importance level of 0.0120. This shows that t count is more prominent than t table (2.56144 > 1.662) with an importance value (0.0120 <0.05). So it can be concluded that Corporate Social Responsibility (X) has a significant effect on the Execution of Monetary (Y). Viewed from consequence testing coefficient certainty, is known that the change in R2 factor free in review is 0.559048 or 55.9%. This implies that 55.9% of Execution Monetary (Y) influenced and could understand by Variable dependent in this review, specifically Corporate Social Responsibility (X). While another 44.1% made sense by various factors in outside regression models.